The Infuence of Leverage and Sales Growth on Financial Distress - Fithri, Elissa; Januarty, Tamy Ali (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
In a dynamic global business environment, companies face enormous challenges to remain competitive and relevant. To achieve the goals of profit maximization and stable growth, companies need to focus on innovation, customer satisfaction and efficient operational management. In this context, financial distress poses a serious threat to the company's continuity, which can lead to bankruptcy if not handled properly. This study aims to measure how much Leverage and Sales growth affect Financial Distress in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023. In this study, Leverage is proxied by the Debt to Equity Ratio, this research uses descriptive and verification data analysis methods with a quantitative research type. The population in this study amounted to 51 companies, using purposive sampling method and obtained a sample of 10 companies. The classic assumption analysis technique, the coefficient of determination, hypothesis testing using the t-test and F-test and processing tools using Eviews 12. Based on partial testing, it shows that Leverage has a negative effect on Financial Distress, and Sales Growth has no effect on Financial Distress, then for simultaneous testing it shows that Leverage and Sales Growth together have an effect on Financial Distress.